Existentialist Reading of Harold Pinter’s Slight Ache in the lens of Sartre - Raouf Aminzadeh; Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani (Britain International for Academic Research (BIAR-Publisher), 2022)
The aim of this study is to discuss use of language, existential anguish and despair and man’s self-quest for identity demonstrate lack of meaning in life in characters in the Slight Ache. Choice and responsibility are two important factors for human life.